Carbon dots labeled Lactiplantibacillus plantarum: a fluorescent multifunctional biocarrier for anticancer drug delivery - Abdullah, Noor A.; Mahmoud, Hoda E.; El-Nikhely, Nefertiti A.; Hussein, Ahmed A.; El-Khordagui, Labiba K. (Frontiers in Bioengineering and Biotechnology, 2023)
A carbon dots (CDs)-biolabeled heat-inactivated Lactiplantibacillus plantarum (HILP) hybrid was investigated as a multifunctional probiotic drug carrier with bioimaging properties. CDs imparted green fluorescence to HILP cells and induced their aggregation as verified by transmission electron microscopy (TEM) and laser scanning confocal microscopy (LCSM). HILP effectively internalized CDs via membrane proteins, forming a biostructure with retained fluorescence in PBS for 3 months at 4oC. Application of CDs/HILP as biocarrier for prodigiosin (PG), an anticancer microbial red pigment, generated a stable green/red bicolor fluorescent combination permitting tracking of both drug carrier and cargo. Cytotoxicity assay using Caco-2 and A549 cells revealed enhanced PG activity by CDs/HILP with synergy at different Fa levels and possible reduction of PG and CDs/HILP doses. LCSM imaging of PG-CDs/HILP-treated Caco-2 cells demonstrated improved cytoplasmic and nuclear distribution of PG as well as nuclear delivery of CDs. The CDs/HILP promoted PG-induced late apoptosis of Caco-2 cells and reduced their migratory ability as affirmed by flow cytometry and scratch assay, respectively. Prediction of PG molecular targets by molecular docking indicated PG interaction with mitogenic molecules involved in proliferation and growth regulation. By allowing visualization of the interaction with cancer cells and promoting the intracellular and nuclear effects of its drug cargo, CDs/HILP offers great promise as an innovative multifunctional nanobiotechnological biocarrier for anticancer drug delivery. This hybrid delivery vehicle merges the physiological activity, cytocompatibility, biotargetability and sustainability of probiotics and the bioimaging and therapeutic potential of CDs.